Factors influencing changes in maxillary arch dimensions in unilateral cleft lip and palate patients until six months of age - Stellzig-Eisenhauer, Angelika; Basdra, Efthimia K.; Hauser, Christine; Haßfeld, Stefan; Komposch, Gerda (The Cleft palate craniofacial journal, 1999)
The objectives of the present study were (1) to investigate whether growth increments until 6 months of age are influenced by particular factors, (2) to analyze whether anterior cleft reduction is dependent on the extent of the cleft width at birth, and (3) to examine the correlation between maxillary measurements at birth and the anterior cleft width at 6 months of age.
Gesehen am 12.02.2021